Demographic Shifts: Exploring the Impacts of Population Ageing in North West India (Prakriti - The International Multidisciplinary Research Journal, 2025)
The demographic landscape in Northwest India is undergoing a transformative shift characterized by population ageing, which poses significant challenges and opportunities for the region. This paper investigates the specific impacts of population ageing on various societal, economic, and healthcare dimensions within the context of Northwest India. Through a comprehensive analysis of demographic trends, socio-economic data, and regional dynamics, we examine the implications of ageing populations on healthcare and intergenerational relationships in the region. Additionally, we explore the cultural and societal factors that influence the experiences of older adults and their families in Northwest India. Furthermore, this paper discusses potential policy responses and interventions tailored to the unique needs and challenges of ageing populations in the region, emphasizing the importance of culturally sensitive approaches and community engagement. By providing insights into the demographic shifts occurring in Northwest India, this research contributes to a deeper understanding of the impacts of population ageing and informs evidence-based strategies for fostering healthy and resilient communities in the region.
Keywords: demographic; em phasizing; analysis